Does The Component of Islamic Financial Literacy Affect on MSMEs Decision in Islamic Banking Financing : Creative Economy Investigate - Habriyanto; Budi Trianto; Nik Hadiyan Nik Azman; Busriadi; Evan Hamzah Muchtar; Elida Elfi Barus (International Journal of Islamic Business and Economics (IJIBEC), 2022)
This study aims to determine what factors influence MSMEs in the creative economy sector in deciding to Islamic Banking financing in Indonesia. We investigated the role of Islamic financial awareness, Islamic financial knowledge and Islamic financial skills. We also examine whether the decision to Islamic Banking financing has an impact on business performance. By using a path analysis approach, the results of this study show that Islamic financial awareness and Islamic financial skills has a positive relationship on decision to financing in Islamic banking. Meanwhile, the decision to financing in Islamic banking has a positive effect on the business performance, but insignificant. Other results show that Islamic financial skills have a positive and significant impact on MSME business performance. The results of this study imply that business actors in the creative economy sector must be given an understanding of Islamic financial skill and Islamic financial awareness. On the other hand, Islamic banking must expand financing in the creative economy sector through a more competitive financing scheme so that it can be easily accessed by MSMEs. The expansion of access to Islamic financing for MSMEs is expected to accelerate the inclusion of Islamic finance in Indonesia.